2013
DOI: 10.1017/s0950268813001556
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and molecular diversity of rabies viruses in Bulgaria

Abstract: A health emergency situation occurred in Bulgaria in 2007 when positive rabies cases were notified in Sofia district in the central-western part of the country, suggesting a southward spread of the disease for the first time in the last 10 years. Phylogenetic analysis on 49 isolates sampled between 2009 and 2011 showed, for the first time, evidence of the existence of NEE and D clustered lineages in Bulgaria. Their geographical distribution clearly reveals the permeability of natural barriers, as already sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
(21 reference statements)
0
11
0
Order By: Relevance
“…Further to the east, rabies virus strains prevalence changes. In Bulgaria, the rabies virus is represented by half of the isolates belonging to the EE sub‐lineage, while the second distinctive lineage clustered with the NEE sub‐lineage (Robardet et al, 2014). In Bulgaria, SF lineage (McElhinney et al, 2011) and D (Robardet et al, 2014) were also confirmed previously.…”
Section: Resultsmentioning
confidence: 99%
“…Further to the east, rabies virus strains prevalence changes. In Bulgaria, the rabies virus is represented by half of the isolates belonging to the EE sub‐lineage, while the second distinctive lineage clustered with the NEE sub‐lineage (Robardet et al, 2014). In Bulgaria, SF lineage (McElhinney et al, 2011) and D (Robardet et al, 2014) were also confirmed previously.…”
Section: Resultsmentioning
confidence: 99%
“…Information on the spread of rabies by animals in Bulgaria dates from 1896, and systematic registration of human cases, morbidity, and lethality has been done since 1928. 7 Rabies is considered eradicated in Bulgaria, as there have been only 6 cases in humans since 1954, with the last one in 1994. This success is the result of integrated efforts and interventions such as induction of compulsory rabies vaccination for domestic dogs in 1949, control of the population of stray animals (dogs, in particular), control of epizootic processes in wild animals, assessment of injuries in humans with carrying out a PEP, which has been applied since 1894 and others.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis could be supported by the fact that mountains can form a substantial barrier to the spread of foxes into a territory, hence this could be a reason for the southwards spread of the disease, from FYROM into Greece, rather than into other areas of that country. However, identification of rabies at high altitudes, recently described in Bulgaria and Italy [5, 19] highlights the permeability of natural barriers. Although red foxes, the most important reservoir for maintenance of rabies in wildlife in Central or South Europe [2, 2023] are well-suited to a wide range of landscapes and can potentially spread rabies in every type of environment, the majority of rabid red foxes (16/40) were recorded in the area of Kilkis at a mean altitude of 210·1 m. Thus, it seems that landscape configuration characterized by gentle slopes influenced animal movement and rabies dissemination.…”
Section: Discussionmentioning
confidence: 99%